Prognostic role of histological regression in primary cutaneous melanoma: a systematic review and meta‐analysis. (15th November 2017) - Gualano, M.R.; Osella‐Abate, S.; Scaioli, G.; Marra, E.; Bert, F.; Faure, E.; Baduel, E.S.; Balagna, E.; Quaglino, P.; Fierro, M.T.; Siliquini, R.; Ribero, S.
Summary: The prognostic significance of histological regression in primary melanoma has been debated for many years. We aim to review the evidence to see how histological regression may affect prognosis. A systematic review was performed by searching in MEDLINE, Scopus and the Cochrane Library from 1 January 1966 to 1 August 2015. All studies reporting hazard ratios or data on survival and histological regression were included. Primary random‐effects meta‐analyses were used to summarize outcome measures. Heterogeneity was assessed using the χ 2 ‐test and I 2 ‐statistic. To assess the potential bias of small studies we used funnel plots and the Begg and Mazumdar adjusted rank correlation method. Summaries of survival outcomes were measured as hazard ratios or relative risk of death at 5 years according to the presence of histological regression of primary melanoma. In total, 183 articles were reviewed out of 1876 retrieved. Ten studies comprising 8557 patients were included. Patients with histological regression had a lower relative risk of death (0·77, 95% confidence interval 0·61–0·97) than those without. Examination of the funnel plot did not provide evidence of publication bias. The results showed that histological regression is a protective factor for survival. Abstract : What's already known about this topic? The prognostic significance of histological regression in primary melanoma has been debated for many years. No robust data are reported on the prognostic value of histological regression. What does this study add? The results of this meta‐analysis may be useful when looking at histological regression in a melanoma. Histological regression may be considered a favourable prognostic factor, probably linked to early activation of the host immune system against the tumour.